1995
DOI: 10.1002/chin.199530264
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Convenient Route to 3′‐Deoxy‐α‐L‐ and 3′‐Deoxy‐β‐D‐ apionucleosides.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…23,25 The D-and L-3′-deoxyapionucleosides 9a−e and 10a−c failed to inhibit DNA or RNA viruses (e.g., HIV-1, HIV-2, HSV-1, HSV-2, VV, and VSV) and, unlike their 2′-deoxy regiomers 6a−c, show no cytotoxicity. 26 Later Jung et al found 9b active against HSV-1(KOS) (MIC 50 = 39.6 μM) and 9e active against HSV-1 in two different cell lines, i.e., KOS and 2(G) (MIC 50 = 7.1 and 35.9 μM, respectively). 27,28 The cytidine congener 11 was shown to be inactive against HIV.…”
Section: Nucleosides With a Transposed 4′-hydroxymethyl Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…23,25 The D-and L-3′-deoxyapionucleosides 9a−e and 10a−c failed to inhibit DNA or RNA viruses (e.g., HIV-1, HIV-2, HSV-1, HSV-2, VV, and VSV) and, unlike their 2′-deoxy regiomers 6a−c, show no cytotoxicity. 26 Later Jung et al found 9b active against HSV-1(KOS) (MIC 50 = 39.6 μM) and 9e active against HSV-1 in two different cell lines, i.e., KOS and 2(G) (MIC 50 = 7.1 and 35.9 μM, respectively). 27,28 The cytidine congener 11 was shown to be inactive against HIV.…”
Section: Nucleosides With a Transposed 4′-hydroxymethyl Groupmentioning
confidence: 99%
“…Barton–McCombie deoxygenation (BMD) is also a popular method to access 3-deoxyapio synthons. One such example is depicted in Scheme and engaged cyclic thionocarbonate 154 , readily available in four steps from the previously mentioned 2,3- O -isopropylidene- d -apio-β- d -furanose ( 151 ) . Although straightforward, this method lacked selectivity, providing a mixture of d - and l -furanosides 155 and 156 , which were separated by chromatography before Vorbrüggen-type base condensation.…”
Section: Chemical Synthesis Of Nucleobase- or 4′-hydroxymethyl-transp...mentioning
confidence: 99%